Honeysuckle : a novel - Fridman-Tell, Bar (Bloomsbury Publishing, 2026)
"Once upon a time, on the edge between meadow and forest, there was a lonely child with only his older sister for company. In exchange for being left in peace, his sister made him a playmate-Daye, a girl woven from flowers and words. And for the first time, this boy, Rory, had a friend. Rory couldn't be happier, until he learns that Daye is a short-lived creature. At the end of each season, she must be woven back together or fall gruesomely apart. And every time Daye falls apart might be her last. As Rory and Daye grow older and the line between friendship and romance begins to blur, Rory becomes desperate to break this cycle of bloom and decay. But the farther Rory pushes his research and experiments to lengthen Daye's existence, the more Daye begins to wonder just how much control she really has over her own life. As a loose reimagining of the story of Blodeuwedd from Welsh mythology, Honeysuckle is an entrancing, inventive, and unsettling debut." -- Jacket flap.